Manajerial Guru Pendidikan Agama Islam dalam Pemberdayaan Organisasi Rohani Islam di SMA Negeri 7 Purworejo - Habib Bahrodin (Cakrawala: Jurnal Kajian Manajemen Pendidikan Islam dan studi sosial, 2020)
This research was conducted based on the importance of the managerial abilities of PAI teachers in fostering and empowering Spiritual Islamic organizations (Rohis) to shape the character of students at SMA Negeri 7 Purworejo. Islamic Religious Education teachers as Spiritual Leaders should have management skills that are needed for the advancement of Rohis organizations. This study aims to reveal and analyze the managerial skills of Islamic Religious Education teachers in empowering Spiritual Islamic organizations (Rohis) in SMA Negeri 7 Purworejo. The theory used in this study is the theory of management skills put forward by Robert L. Katz regarding conceptual skills, human skills and technical skills. In conducting this research, researchers used a qualitative approach by using interview techniques with coaches, administrators and spiritual members, namely PAI teachers and students. Researchers also made direct observations in the environment of SMA Negeri 7 Purworejo. Based on the results of the research and discussion, a number of things were found: First, the conceptual skills of PAI Teachers in empowering Spiritual organizations are carried out through their skills in determining strategies, making policies, preparing program plans and their skills in decision making. Second, the human skills of PAI teachers in empowering Rohis organizations are carried out through their skills in building communication, increasing work morale, creating an organizational climate, assessing organizational performance, and their skills in building the character of Rohis members. Third, the technical skills of PAI teachers are carried out through their skills in creating learning students, organizing and managing learning resources, increasing alumni and community participation, increasing collaboration with similar institutions, and skills in managing organizational administration. Of the overall managerial skills possessed by the PAI teacher, it can be stated that the PAI teacher as an education manager has been able to properly manage and empower the Rohis organization at SMA Negeri 7 Purworejo because he has applied the skills needed to advance an organization.